Ahmad Surkati: Pelopor Pembaharuan Kajian Hadis di Indonesia: Ahmad Surkati: Pioneer of Renewal in Hadith Studies in Indonesia - Abdullah, Abdullah; Zulfahmi Alwi; Siti Aisyah (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2025)
The article discusses the significant role of Ahmad Surkati as a pioneer in the renewal of hadith studies in Indonesia. It examines Surkati's intellectual journey, highlights his contributions to hadith studies, and explores their impact on the development of hadith understanding among the community. By detailing the analytical approach employed by Surkati, the article describes how he encourages the community to uphold the pure teachings of Islam derived from the Qur'an and hadith. Additionally, the article addresses the challenges faced by Surkati in conveying understanding and values within Indonesian society at that time, where practices such as innovation, superstition, discrimination, and blind imitation had become prevalent among the Muslim community. In conclusion, this research provides profound insights into Ahmad Surkati's key role in shaping the discourse of hadith studies in Indonesia and promoting a renewal in the classical approach to understanding hadith.